(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study was done to determine the drug resistance pattern and Extended Spectrum β-Lactamase (ESBL) in bacterial isolates of Enterobacteriaceae family from different clinical specimens. Methods: The isolates were identified by conventional culture techniques and subjected to antimicrobial susceptibility testing by modified Kirby Bauer disk diffusion methods and ESBL detection by combined disk method. Results: Of the total 1602 sample processed 200 (12.5%) bacteria of Enterobacteriaceae family were isolated and 85.5% of them were multidrug resistant. Of the total Enterobacteriaceae isolates 27% were ESBL producers. Single isolate of stool was MDR and ESBL producer. Higher prevalence of MDR isolates (100%) and ESBL producer (41.2%) was observed in sputum specimen. Higher multidrug resistance (92.1%) and ESBL production (35%) was detected in Klebsiella pneumoniae. Conclusion: The most effective antibiotics towards the isolates of Enterobacteriaceae were imipenem, amikacin, chloramphenicol and tetracycline. Emergence of MDR and ESBL producing Enterobacteriaceae requires proper infection control measures and routine and reliable detection of ESBL with rationale use of antibiotics.